DB-HERITAGE Building Materials Data Aggregation in ARIADNE - challenges and opportunities - Maria J. Correia; António Santos Silva (Internet Archaeology, 2023)
DB-HERITAGE provides open and free sharing of wide-ranging technical data on hundreds of samples of building materials from diverse periods, extracted from Portuguese built heritage all over the world. It has been developed to improve know-how for historic building materials and as a basis for developing best practices for built heritage conservation. It incorporates both physical and digital repositories for building material samples and related data, providing tools for the systematic recording of data concerning the history, properties, and performance of materials used in Portuguese built heritage.